KEDUDUKAN AKTA NOTARIS YANG DIANGGAP TIDAK MEMILIKI KEKUATAN HUKUM SAH ATAU BATAL DEMI HUKUM - Muhammad Rizki Ramadhan (Universitas 17 Agustus 1945 Samarinda, 2021)
ABSTRACTThrough an authentic deed thatclearly defines rights andobligations guarantee legalcertainty, and at the same time it ishoped that disputes can be avoided.In the dispute resolution process, thean authentic deed which is the strongestand most fulfilled written evidencegives a real contribution to thesettlement of cases cheaply andquickly. In a juridical sense, the proof isonly needed in a case before theThe court, be it a civil or criminal case,thus, if there is no dispute, the proofis not necessary. In this research, thethe writer will discuss the problemregarding, What is the responsibilityof a notary as a General Officer fornotary deeds as evidence which isconsidered invalid or legally flawed?Where the purpose of this research isto find out how the responsibility ofthe notary as a general office to thenotary deed as evidence which isconsidered invalid or legally flawed.In writing this research, the juridicalnormative approach is used, whichfocuses on literature research thatdescribes secondary data, namelyprimary legal materials in the formof laws and regulations, secondarylegal materials such as books andscientific papers are written by legalexperts and related to the topic.research and tertiary legal materialsin the form of a Big IndonesianDictionary and a Legal LanguageDictionary. The scope of thisresearch is on issues related to thepower of proof of deeds, therefunctions and roles. This study aimsto investigate, discuss, describe andpresent a problemrelated to the power of proof of aNotary's deed. The problem raised inthis paper is entitled